2019
DOI: 10.11606/s1518-8787.2019053000915
|View full text |Cite
|
Sign up to set email alerts
|

Adapted version of the Pubertal Development Scale for use in Brazil

Abstract: OBJECTIVE: To determine whether scores in an adapted version of the self-assessment Pubertal Development Scale into Portuguese match those from the gold standard in pubertal development (Tanner scale). METHODS: This was a cross-sectional study with a convenience sample of 133 children and adolescents aged nine to 17 years (59 males; mean age of 13 years and six months, with standard deviation = 25 months). Youngsters completed the Pubertal Development Scale and were then examined by specialists in adolescent m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Few studies have reported the agreement between youth-assessed puberty using the PDS and clinicianassessed puberty [13,14,27,28]. Furthermore, comparing the current study to those in the literature is problematic owing to the use of different agreement statistics and to the use of five-point over three-point puberty development scales.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Few studies have reported the agreement between youth-assessed puberty using the PDS and clinicianassessed puberty [13,14,27,28]. Furthermore, comparing the current study to those in the literature is problematic owing to the use of different agreement statistics and to the use of five-point over three-point puberty development scales.…”
Section: Discussionmentioning
confidence: 83%
“…One study conducted in the USA reported a moderate strength of agreement (κ = 0.57; 95% CI: 0.49-0.66), but this kappa coefficient was unweighted and not stratified by sex thereby limiting the sex-wise comparison to the current study [27]. Conversely, a Brazilian study reported high levels of agreement but used intraclass correlation coefficients of 0.82 for boys (95% CI: 0.70-0.90) and of 0.81 for girls (95% CI: 0.70-0.89) [13]. Older PDS agreement studies map the PDS onto the five-point Tanner stages.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Informed participant assent was always confirmed before test administration. Participants answered a socio-demographic questionnaire, self-evaluated their puberal status filling in the 5-item Pubertal Development Scale [PDS, adapted from Carskadon et al, 1993 into Portuguese by Pompéia, 2019 ] and were administered the FREE executive function tasks in four pseudorandom orders to avoid the effects of fatigue. Participants from the supervised online group (hereafter called as “online group”) were recruited through contact from their schools and social media after the authorities introduced social distancing and closed schools due to the COVID-19 pandemic.…”
Section: Methodsmentioning
confidence: 99%
“…Pubertal status was self-assessed using the PDS, adapted from Carskadon and Acebo (1993) for local use by Pompeia et al (2019). The scale contains a series of questions regarding the development of secondary sexual characteristics, assessing characteristics related to both gonadal and adrenal factors: body hair development, growth spurt and skin changes for participants of both sexes, voice changes and facial hair growth for boys, and breast growth in girls.…”
Section: Methodsmentioning
confidence: 99%